2015
DOI: 10.9738/intsurg-d-14-00086.1
|View full text |Cite
|
Sign up to set email alerts
|

Higher Level of Serum Heme Oxygenase-1 in Patients With Intracerebral Hemorrhage

Abstract: The objective of this paper was to investigate the association of the serum level of heme oxygenase-1 in patients with intracerebral hemorrhage (ICH) with the risk of ICH. Heme oxygenase-1(HO-1) metabolizes heme into biliverdin, bilirubin, carbon monoxide, and iron, our recent study showed that serum level of HO-1 was increased in stroke patients, yet the association of HO-1 level with risk of intracerebral hemorrhage (ICH) is poorly known. Forty patients with ICH and another 40 patients without ICH were recru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 14 publications
(16 reference statements)
1
15
0
Order By: Relevance
“…At postoperative 30 minutes, ICH rats were treated with 10 mg/kg ZPP and at postoperative day 3, rats were sacrificed and parameters were evaluated. Results showed that HO-1 positive rate and mRNA expression of rats in the ICH group were significantly increased, which is consistent with the study done by Wang et al,9 Li et al17 and Liu et al,18 while ZPP significantly reduced brain tissue HO-1 expression in post ICH rats. Our study also showed that ZPP as HO-1 inhibitor could significantly reduce the neurological function deficit score and brain water content in ICH rats, suggesting that overexpression of HO-1 at day 3 post ICH has an inhibitory effect on the recovery of neurological function and relief of brain edema.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…At postoperative 30 minutes, ICH rats were treated with 10 mg/kg ZPP and at postoperative day 3, rats were sacrificed and parameters were evaluated. Results showed that HO-1 positive rate and mRNA expression of rats in the ICH group were significantly increased, which is consistent with the study done by Wang et al,9 Li et al17 and Liu et al,18 while ZPP significantly reduced brain tissue HO-1 expression in post ICH rats. Our study also showed that ZPP as HO-1 inhibitor could significantly reduce the neurological function deficit score and brain water content in ICH rats, suggesting that overexpression of HO-1 at day 3 post ICH has an inhibitory effect on the recovery of neurological function and relief of brain edema.…”
Section: Discussionsupporting
confidence: 91%
“…In a study done by Li et al17 on the level of HO-1 in plasma and total bilirubin in 40 cases of ICH patients and 40 healthy controls, results showed that levels of HO-1 and total bilirubin were significantly higher in the ICH group compared to healthy controls. Multiple regression analysis showed that HO-1 and total bilirubin is closely related to ICH patients.…”
Section: Discussionmentioning
confidence: 93%
“…Interestingly, the role of HO1 after ICH is controversial [5]. In ICH patients, HO1 expression in the hemorrhagic brain is associated with CD163 expression at 72 h after ICH [49], and serum HO1 level is increased in ICH patients [50]. In an animal model of ICH, systemic hemin therapy was reported to increase HO1 expression and attenuate blood-brain barrier disruption [51].…”
Section: Discussionmentioning
confidence: 99%
“…Such molecular changes could be detected by serum biomarkers. For example, interleukin 6 (IL-6) [ 23 26 ] and intercellular adhesion molecule (ICAM-1) could represent the inflammation level [ 23 , 27 , 28 ], 8-hydroxy-2′-deoxyguanosine (8-OHdG) [ 29 , 30 ] and heme oxygenase-1 (HO-1) could provide the information of oxidative stress [ 31 35 ], and brain-derived neurotrophic factor (BDNF) could be an indicator of neuroplasticity [ 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%